Dynamic association of capping enzymes with transcribing RNA polymerase II - Schroeder, Stephanie C. (Cold Spring Harbor Laboratory Press, 2000)
The C-terminal heptad repeat domain (CTD) of RNA polymerase II (pol II) is proposed to target pre-mRNA processing enzymes to nascent pol II transcripts, but this idea has not been directly tested in vivo. In vitro, the yeast mRNA capping enzymes Ceg1 and Abd1 bind specifically to the phosphorylated CTD. Here we show that yeast capping enzymes cross-link in vivo to the 5′ ends of transcribed genes and that this localization requires the CTD. Both the extent of CTD phosphorylation at Ser 5 of the heptad repeat and the binding of capping enzymes decreased as polymerase moved from the 5′ to the 3′ ends of the ACT1, ENO2, TEF1, GAL1, and GAL10 genes. Ceg1 is released early in elongation, but Abd1 can travel with transcribing pol II as far as the 3′ end of a gene. The CTD kinase, Kin28, is required for binding, and the CTD phosphatase, Fcp1, is required for dissociation of capping enzymes from the elongation complex. CTD phosphorylation and dephosphorylation therefore control the association of capping enzymes with pol II as it transcribes a gene.